Ethical leadership for a better education system : What Kind of People Are We? - Roberts, Carolyn (Routledge, 2019)
"How can head teachers live up to expectations? What makes them fail? What keeps the profession in good standing in the taxpayer's eye, and what undermines it? This book sets out a new vision for school leadership, moving beyond leadership styles and best practice to reflect on the intrinsic motivation in becoming a leader within a school setting, and proposing a way for the profession to develop and maintain ethical standards. Chapters explore the 2017-18 Commission on Ethical Leadership in Schools, considering the core principles and behaviours we should expect from our school leaders, and providing a clear, ethical code for thinking about and reinforcing ethical standards in schools"- Resumé vydavatel
Keywords: management školy -- etické a morální aspekty -- Velká Británie; ředitelé škol -- etické a morální aspekty -- Velká Británie; school principals -- ethical and moral aspects -- Great Britain; elektronické knihy; monografie; electronic books; monographs